Predictors of self- and caregiver-rated quality of life for people with dementia living in the community and in nursing homes in northern Taiwan. (May 2015) - Huang, Hsiu-Li; Weng, Li-Chueh; Tsai, Yu-Hsia; Chiu, Yi-Chen (Yulanda); Chen, Kang-Hua; Huang, Chin-Chang; Tang, John Sai-Hung; Wang, Woan-Shyuan
ABSTRACT Background: Factors affecting quality of life (QOL) ratings for people with dementia (PWD) have been well studied, but few studies have examined the effect of residence on PWD- and caregiver-rated QOL for PWDs. We designed this study to determine the factors related to PWD- and caregiver-rated QOL in dementia as well as factors related to the discrepancy in these ratings. Methods: For this cross-sectional study, we analyzed data from a convenience sample of 106 PWD-family caregiver dyads (58 community-dwelling dyads and 48 nursing-home dyads). PWDs' data included socio-demographic variables, QOL (assessed by the Quality of Life-Alzheimer's Disease [QOL-AD] scale), cognition, dementia severity, depression, comorbidities, and quality of the dyadic relationship. Caregivers' data included socio-demographic variables, depressive symptoms, and mutuality of the dyadic relationship. Results: QOL-AD scores were lower when rated by caregivers than by PWDs. The key factors positively related to both PWD- and caregiver-rated QOL for PWDs were fewer PWD depressive symptoms and higher quality of the PWD-caregiver relationship. The key factors related to the discrepancy in PWD- and caregiver-rated QOL in dementia were PWD residence in a nursing home and lower dementia severity, as well as higher caregiver depression, being an adult child caregiver, and lower caregiver-PWD mutuality. Conclusion: Caregiver-rated QOL for PWDs and the discrepancy in rated QOL were significantly associated with PWD residence. If caregiver-rated QOL is needed, the effect of residence of PWD should be taken into consideration. Caregivers' depressive status and mutuality with PWD must be also carefully assessed.